Influence of composite resin volume and C-factor on the polymerization shrinkage stress - Mondelli, Rafael Francisco Lia; Velo, Marilia Mattar de Amoêdo Campos; Gonçalves, Rafael Simões; Tostes, Bhenya Ottoni; Ishikiriama, Sergio Kiyoshi; Bombonatti, Juliana Fraga (Brazilian Dental Science, 2016)
Objective: Composite polymerization shrinkagestress is an inherent process of chemical and lightcomposite resin activation. Consequently, this fact hasbeen associated to potential clinical problems. Theaim of the present in vitro study was to evaluate thevolume and C-factor influence on chemical and lightcuringcomposite resin polymerization shrinkagestress, using a non-rigid method that thereby provideslower stress values, causing a minimal deflection inload cell. Materials and Methods: The contractionforces of the Z-250 and Concise composite resinsduring polymerization were recorded in an UTM intwo experiments. In the first experiment, the Z-250composite was inserted beetwen two rectangularsteel plates (6.0 x 2.0 mm), varyng the resin volumesand C-factors, in a single increment, polymerized for20 s and the forces generated were recorded for 120s. In the second experiment, a pair of rectangular steelplates (3x2mm) and two square steel plates (2x2mm),with varied heights (2; 3 mm, respectively), wereused to determine the C-factor (0.6; 0.3) influence.Results: The polymerized Z-250 results showed thatthe volume variations, independent of the C-factor,had a direct influence on the shrinkage stress,different from the Concise, which was influenced bythe C-factor. Conclusion: The present study showedthat a higher volume of composite resins determinesan increase in the shrinkage stress of light-curingcomposites.KeywordsC-factor. Composite resin. Polymerization. Shrinkagestress.